Home round: a strategy for improving community health - Dotimi, Doris A.; Silas, Joel Usen; Wamanyi, Yohanna (International Journal Of Community Medicine And Public Health, 2024)
In community health practice, home rounds are essential. In Nigeria, a home round is a regular visit to outpatients/clients in their homes by a team of community health specialists to make decisions concerning patient/client’s care, review, and follow-up on the progress of their health condition. The team visits within the treatment period to make sure the patient is adhering to prescriptions, address any barriers to care, and make referrals if necessary. Home rounds start with examining patient records, putting together a team, assessing patients in their homes, and recording the findings and actions. A competent community health practitioner (CHP) should be compassionate, informed, and skillful at conducting house rounds, identifying family health problems, and taking the necessary action. In primary health care, home rounds can detect less common but serious individual and family conditions; and enhance community health. However, challenges like shortage of manpower, insecurity, lack of logistics, and unskillful health workers have made home rounds impossible in some primary healthcare facilities. To facilitate home rounds, it is recommended that governmental and nongovernmental organizations train community health practitioners in home rounding, provide logistics at primary healthcare facilities, and staff each health center with a sufficient number of community health practitioners by primary healthcare standards. Community health practitioners should be adaptable, sensitive, and skilled, and families and communities should work together to provide security.